Foreign investment in Vietnam : Juridical bases - Present state - Opportunities - Prospects - Nguyen Anh Tuan (The gioi, 1994)
Content: Juridical aspect of foreign investment activities in Vietnam; Foreign in vestment activities in Vietnam in the years 1988-1993; Export production zones in Vietnam; Prospects of foreign investmenr in Vietnam until 2000